Peran Kepemimpinan Publik pada Transformasi Sistem Perpajakan dan Dampaknya bagi Konsultan Pajak - Eriyanti Eriyanti; Sinta Nurfatimah; Rakim Adiwijaya; Sylviana Murni; Antony Ludfi Arifin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The transformation of tax administration through the use of digital technology is an essential part of fiscal bureaucratic reform aimed at improving efficiency, transparency, and taxpayer compliance, the success of which is strongly influenced by the role of public leadership. This study aims to analyze the role of public leadership in driving the transformation of the tax administration system through the implementation of the CoreTax Administration System and to examine its implications for changes in the functions, competencies, and work patterns of tax consultants. The study employs a qualitative method with a literature review and policy analysis approach by examining tax regulations, official government reports, and scientific publications related to tax reform and the digitalization of tax administration. The findings indicate that the implementation of the CoreTax Administration System, both conceptually and operationally, is capable of improving administrative efficiency, data management accuracy, and consistency in monitoring taxpayer compliance through automated system integration. The results further emphasize that visionary, adaptive, and responsive public leadership plays a strategic role in maintaining reform consistency, strengthening the regulatory framework, and ensuring transparent and accountable digital governance. This digital transformation has driven a shift in the role of tax consultants from conventional administrative functions toward data-driven strategic advisory services, policy interpretation, and digital compliance assistance. The study concludes that the success of tax administration reform is determined not only by the capacity of the fiscal bureaucracy but also by the ability of tax consultants to enhance technological competencies and adapt to the dynamics of the digital tax system, although this study remains limited to the early stage of implementation, thereby requiring further research to assess long-term impacts and taxpayer behavioral readiness.